VALUE ADDED INTELLECTUAL COEFFICIENT TERHADAP KONSERVATISME AKUNTANSI - Soenarno, Yanuar Nanok; Kheay, Septina (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2025)
This study aims to examine the influence of Value Added Intellectual Capital (VAIC) on accounting conservatism in mining companies listed on the Indonesia Stock Exchange. The research utilizes data from manufacturing firms listed on the exchange for the year 2021. A simple linear regression model was employed, with SPSS 22 used for data analysis. The findings reveal a negative relationship between VAIC and accounting conservatism. This indicates that the more efficiently a company manages its intellectual capital, the lower its tendency to apply conservative accounting practices. In other words, firms with high intellectual efficiency are more likely to present financial reports that reflect economic value and future prospects rather than excessive prudence.